EXPLORING HIGH SCHOOL STUDENTS’ AFFECTIVE RESPONSES TOWARD AUTHENTIC TEXTS IN READING ACTIVITIES : A CASE STUDY IN MALANG INDONESIA - Khoir, Azizatul; Badriyah, Ima Mutholliatil; Ariani, Faridah (Universitas Muhammadiyah Metro, 2026)
Reading is a complex language skill because it involves various cognitive and affective processes in understanding text. This study attempts to analyze the students' affective responses and the challenges faced by them while reading authentic English texts at a high school level. This study applied a qualitative method with a case study approach. The subjects of this study were tenth-grade students at a high school in Malang. The research data was obtained through observation, questionnaires, and interviews, which showed that students’ affective responses to the use of authentic texts in reading activities were divided into five aspects, namely receiving (3.77, high category), responding (3.37, medium category), valuing (4.04, high category), organization (3.64, high category), and characterization (3.17, medium category). However, the students also faced several challenges, especially regarding some problematic vocabulary, sentence structures, and cultural understanding of the texts. This study is expected to provide useful information for the development of reading activities based on authentic texts, and this could serve as a reference for further research conducted in the context of authentic text use.